1998
DOI: 10.1182/blood.v91.12.4747.412k41_4747_4751
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Related Protein-Induced Hypercalcemia in SCID Mice Engrafted With Adult T-Cell Leukemia Cells

Abstract: Parathyroid hormone-related protein (PTHrP) is considered to be one of the main causes of hypercalcemia associated with adult T-cell leukemia (ATL). To clarify the role of PTHrP and bone remodeling in the development of hypercalcemia in ATL, we examined the SCID mouse model of ATL that has previously been shown to mimic the disease in humans. Using this model, we found clear elevations in serum levels of calcium and C-terminal PTHrP (C-PTHrP). PTHrP mRNA was highly expressed in ATL cells proliferating in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
14
2
Order By: Relevance
“…These results indicate that MIP‐1α plays an important role in hypercalcemia in patients with ATL. However, because PTHrP has emerged as an important factor in the pathogenesis of hypercalcemia in ATL patients, (4,10) our findings in this study are contradictory to those previous observations. Previous studies reported that PTHrP cannot directly induce differentiation of hematopoietic precursor cells to osteoclasts and that high levels of PTHrP in the serum are not always associated with hypercalcemia in patients with ATL (11,12) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results indicate that MIP‐1α plays an important role in hypercalcemia in patients with ATL. However, because PTHrP has emerged as an important factor in the pathogenesis of hypercalcemia in ATL patients, (4,10) our findings in this study are contradictory to those previous observations. Previous studies reported that PTHrP cannot directly induce differentiation of hematopoietic precursor cells to osteoclasts and that high levels of PTHrP in the serum are not always associated with hypercalcemia in patients with ATL (11,12) .…”
Section: Discussioncontrasting
confidence: 99%
“…Among these factors, PTHrP is considered to play an important role in stimulating osteoclasts, resulting in increased bone resorption. Immunodeficient mice implanted with leukemic cells from patients with ATL exhibited hypercalcemia and overexpressed PTHrP (10) . However, PTHrP cannot directly induce the differentiation of hematopoietic precursor cells to osteoclasts (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Additional techniques used to study the pathogenesis of HHM include the infusion of bioactive molecules (e.g., synthetic PTHrP) and the induction of squamous cell carcinoma by cutaneous application of dimethylbenzanthracene [50,118]. [127][128][129] Squamous cell carcinoma [128,130] Renal cell carcinoma [131,132] Urothelial cancer [133] Esophageal carcinoma [134,135] Melanoma [136,137] Mammary cancer [138] Pancreatic cancer [139] Colon cancer [140,141] Ovarian cancer [142] Adult T-cell leukemia/lymphoma SCID, NOD/scid [143][144][145] Multiple myeloma [146,147] Ovarian cancer [148] Allogenic models: The allogenic HSDM1 fibrosarcoma was derived from a mouse and results in progressive hypercalcemia 2-3 weeks following serial transfer into Swiss albino mice [119]. Evidence suggests that prostaglandin E 2 (PGE 2 ) is responsible for mediating the hypercalcemia, which is a unique, but uncommon mechanism of HHM.…”
Section: Mouse Models Of Cahmentioning
confidence: 99%
“…Adult T-cell leukemia/lymphoma (ATL): RVATL, MET-1, primary ATL cells: Immunodeficient SCID mice injected intraperitoneally with primary human ATL cells develop hypercalcemia and increased serum PTHrP concentrations [ 145 ]. The RV-ATL cells were derived from an ATL patient [ 163 ] and, when injected intraperitoneally into SCID/beige or NOD/scid mice, developed multicentric lymphoma, ascites and HHM.…”
Section: Mouse Models Of Cahmentioning
confidence: 99%